2015 Physics Education Research Conference Proceedings 2015
DOI: 10.1119/perc.2015.pr.089
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Centrality: Investigating Student Outcomes within a Classroom Social Network

Abstract: Abstract. Collaborative learning environments in undergraduate introductory physics courses, such as those promoted by Modeling Instruction (MI), influence both student performance and student social interactions. Because collaborative learning is inherently a social activity, we applied Network Analysis methods to examine student social interactions within the classroom using a survey administered periodically in class. We then calculated centrality, which is a family of measures that quantify how connected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…We propose that both directions of this influential pathway are possible. We claim that student engagement and academic performance exhibit a relationship that is reciprocal and iterative, i.e., that past performance influences engagement which in turn influences future performance [22,41]. Therefore, we hypothesize that student engagement in the MI classroom will predict future academic performance even when controlling for prior qualifications.…”
Section: B the Relationship Between Engagement And Performancementioning
confidence: 95%
“…We propose that both directions of this influential pathway are possible. We claim that student engagement and academic performance exhibit a relationship that is reciprocal and iterative, i.e., that past performance influences engagement which in turn influences future performance [22,41]. Therefore, we hypothesize that student engagement in the MI classroom will predict future academic performance even when controlling for prior qualifications.…”
Section: B the Relationship Between Engagement And Performancementioning
confidence: 95%
“…Here, we focus on the network of interactions captured by forum data-not just how often a student participated, but their conversation partners and overall prominence in the aggregated structure of threads. Past results from social network analysis, outlined below, suggest that the most central students in this network may experience better course outcomes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of university physics courses, social network analysis (SNA) has been used to contrast different classroom types [7], to explore connections between student networks and success measures [4][5][6], and to trace the development of student communities [8,9]. More broadly, studies of online course discussion forums have linked student participation in a forum network with sense of course community [10] and found that forums with a high amount of student social structure can demonstrate higher levels of critical thinking [11].…”
Section: Introductionmentioning
confidence: 99%
“…Founded on previous SNA instruments, 16,18,39 it substantially improves measuring the intricacies of student social connections. Deploying an existing instrument was cumbersome for both participants and practitioners.…”
Section: Discussion and Implications For Researchmentioning
confidence: 99%
“…[16][17][18][19] Typically these efforts concentrate on the nature of the interactions and the interpersonal/intergroup dynamics. 14,[20][21][22][23] Examination at this micro-level is vital to understanding how relationships are formed, but tends to ignore the larger social structures of an environment.…”
Section: Introductionmentioning
confidence: 99%